Study of Selected Rice (Oryza sativa) Producing Soil Characteristics of Wukari, North-Eastern Nigeria - Jacob Usman; Adashu Tanko Gani (Bulgarian Journal of Soil Science)
The study examining the soil's characteristics for sustainable rice (Oryza sativa) production. The soils featured a sandy clay loam, loamy sand, and sandy loam texture. They were also deep and well-drained. Their pH values ranged from 5.00 to 5.70, indicating that they were generally somewhat acidic in response. The majority of the crops in the study area can be produced sustainably within this pH range. The pH of the soil often controls the availability and unavailability of the majority of nutrient components in agricultural productivity. It also controls how these nutrients are absorbed for a steady crop supply. Additionally, the soils' nutritional (OC, OM, TN & P) concentration was poor. While exchangeable cations (Ca2+, Mg2+, K+ , and Na+ ) were limiting variables in the research area, the percentage base saturation was high. A moderately suitable (S2) unit I and marginally suitable (S3) units II rating for rice cultivation was found in the suitability assessment of a few chosen Wukari soils. For increased rice yield in the area under study, significant soil amendment or management techniques specifically, the use of organic or inorganic fertilizer and planting timing have been suggested.